Ali Cross - Book 1 - Patterson, James 1947-; Little, Brown and Company (New York : Jimmy Patterson Books/Little, Brown and Company, 2019)
Alex Cross son, Ali, is eager to follow in his fathers footsteps as a detective, but when his best friend goes missing, what price will he have to pay to solve the mystery?
Keywords: Child detectives -- Juvenile fiction; Middle school students -- Juvenile fiction; Missing persons -- Investigation; Juvenile fiction; Child detectives -- Fiction; Middle school students -- Fiction; Missing persons -- Fiction; Child detectives -- Fiction; Middle school students -- Fiction; Missing persons -- Investigation; Fiction; Washington (D.C.) -- Juvenile fiction; Washington (D.C.) -- Fiction; Washington (D.C.) -- Fiction